Evaluation of The Antioxidant, Antimicrobial, and Anticancer Activities of Dicliptera bupleuroides Isolated Compounds Using In Vitro and In Silico Studies - Shehla Akbar; Saiqa Ishtiaq; Muhammad Jahangir; Sameh S. Elhady; Hanin A. Bogari; Abdelrahman M. Alahdal; Mohamed L. Ashour; Fadia S. Youssef (Molecules, 2021)
Phytochemical investigation of chloroform fraction (DBC) and ethyl acetate fraction (DBE) of D. bupleuroides (Acanthaceae) resulted in the isolation of β-sitosterol (1) from DBC and vanillic acid (2) from DBE, which were first to be isolated from D. bupleuroides. β-Sitosterol (1) exhibited substantial antioxidant activity (IC50 = 198.87 µg/mL), whereas vanillic acid (2) showed significant antioxidant power (IC50 = 92.68 µg/mL) employing 1,1-diphenyl-2-picrylhydrazyl (DPPH*) radical scavenging capacity assay. Both compounds showed pronounced antimicrobial activity using the agar disc diffusion method, particularly against fungi showing MIC values of 0.182 and 0.02 concerning Candida albicans, respectively, and 0.001 mg/mL regarding Penicillium notatum. They revealed considerable antibacterial activity with MIC values ranging between 0.467 and 0.809 mg/mL. Vanillic acid (2) exhibited substantial anticancer potential displaying 48.67% cell viability at a concentration of 100 μg/mL using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-Diphenyl-2H-Tetrazolium Bromide) assay concerning HepG2 cell lines. These results were further consolidated by in silico studies on different enzymes, where vanillic acid displayed a high fitting score in the active pockets of DNA-gyrase, dihydrofolate reductase, aminoglycoside nucleotidyltransferase, and β-lactamase. It also inhibited human cyclin-dependent kinase 2 (CDK-2) and DNA topoisomerase II, as revealed by the in silico studies. ADME/TOPKAT (absorption, distribution, metabolism, excretion, and toxicity) prediction showed that vanillic acid exhibited reasonable pharmacodynamic, pharmacokinetic, and toxicity properties and, thus, could perfectly together with D. bupleuroides crude extract be incorporated in pharmaceutical preparations to counteract cancer and microbial invasion, as well as oxidative stress. Thus, it is concluded that D. bupleroides could be a potential source of therapeutically active compounds, which would be helpful for the discovery of clinically effective and safe drugs.